2022
DOI: 10.1093/oxfimm/iqac002
|View full text |Cite
|
Sign up to set email alerts
|

Is ‘Long Covid’ similar to ‘Long SARS’?

Abstract: and Lay Abstract Is “Long Covid” similar to “Long SARS” (Severe Acute Respiratory Syndrome)? In 2019, a new pandemic started, and is still ongoing. The causative virus is the only known close relative of the SARS coronavirus (SARS-CoV-1), and is accordingly called SARS-CoV-2. Follow-up for between 2 and 10 years of 50 post SARS patients in a rehabilitation setting led to publications and clinical impressions that are summarized here regarding significant permanent disability for some of these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Our study showed a high prevalence of symptoms that were also characteristic of long-SARS [39] , [40] , anticipating that full recovery could also be difficult to achieve for many long COVID patients. Currently, in addition to health costs relative to acute infection, there is an increasing burden derived from the treatment of long-term sequelae.…”
Section: Discussionmentioning
confidence: 70%
“…Our study showed a high prevalence of symptoms that were also characteristic of long-SARS [39] , [40] , anticipating that full recovery could also be difficult to achieve for many long COVID patients. Currently, in addition to health costs relative to acute infection, there is an increasing burden derived from the treatment of long-term sequelae.…”
Section: Discussionmentioning
confidence: 70%
“…The literature has suggested a common course for post-acute COVID-19 and SARS and thus a hypothetical shared post-coronavirus symptomatology. As noted by Patcai, a subset of SARS patients at their hospital developed "long SARS," a non-specific, ill-defined condition bearing many similarities to PASC [96]. Neurological complications are rarely observed during follow-ups of SARS patients, but cases of musculoskeletal disorders and peripheral neuropathy have been described [97,98].…”
Section: Sars-cov-1mentioning
confidence: 99%
“…Overall, the scant reports of SARS-CoV-1-associated neurological sequelae contrast strikingly with the high proportion of COVID-19 patients who go on to experience NC-PASC [14]. Headache, inattention [2,10], cognitive impairment [15], memory impairment, peripheral nerve disorders (including Guillain-Barré syndrome), movement disorders, stroke [16], numbness/tingling, dysgeusia, anosmia, dizziness, blurry vision, and tinnitus [17] SARS-CoV-1 Coronaviridae Respiratory tract epithelial cells [95] Cognitive impairment, sleep disturbance [96], neuromusculoskeletal disorders [97], peripheral neuropathy [98], Guillain-Barré syndrome, and stroke [94] HSV-1, HSV-2, VZV Herpesvirinae Epithelial cells, sensory ganglia during latency [101] Herpes labialis (cold sores), herpes zoster (shingles), and encephalitis [102] EBV Herpesvirinae B cells, nasopharyngeal epithelial cells, and CNS neuronal cells [103] Combative behavior, seizures, headache [104], "Alice in Wonderland" syndrome, facial nerve palsy, progressive microcephaly, and encephalitic illness [105,106] CMV Herpesvirinae Epithelial cells, endothelial cells, fibroblasts, smooth muscle cells [107],…”
Section: Sars-cov-1mentioning
confidence: 99%
“…Post-viral syndromes are nothing new [16,17]. We already knew of the significant ongoing burden of disease in many infected with SARS-CoV-1 almost 20 years [18] and MERS over 10 years ago [19]. The chances that another new coronavirus like SARS-CoV-2 would causes significant long term morbidity should have been a consideration from the very beginning of the pandemic.…”
mentioning
confidence: 99%